Radiation and Mass Transfer Effects on MHD Free Convection Flow of a Micropolar Fluid past a Stretching Surface Embedded in a Non-Darcian Porous Medium with Heat Generation. (21st February 2013) - Ibrahim, S. Mohammed; Reddy, T. Sankar; Reddy, N. Bhaskar
Abstract : A comprehensive study of mass transfer and thermal radiation on a steady two-dimensional laminar flow of a viscous incompressible electrically conducting micropolar fluid past a stretching surface embedded in a non-Darcian porous medium in the presence of heat generation is analyzed numerically. The governing equations of momentum, angular momentum, energy, and species equations are solved numerically using Runge-Kutta fourth order method with the shooting technique. The effects of various parameters on the velocity, microrotation, temperature and concentration field as well as skin friction coefficient, Nusselt number and Sherwood number are shown graphically and tabulated. It is observed that the micropolar fluid helps in the reduction of drag forces and also acts as a cooling agent.